ANALYSIS OF METHODS OF PREVENTION OF INTRA- AND POSTOPERATIVE COMPLICATIONS DURING TOOTH EXTRACTION - Lokes, K.P.; Avetikov, H.D.; Ivanytska, O.S.; Steblovskyi, D.V.; Skikevych, M.G.; Ivanytskyi, I.O.; Avetikov, D.S. (World of Medicine and Biology, 2024)
The literature data notes a compilation rate of 4.6–30.9 % after this surgical intervention, which can occur intraoperatively or develop during the postoperative period and can be general or local in nature. The purpose of the study was to conduct an analysis of methods of prevention of complications of tooth extraction surgery by analyzing domestic and foreign literary sources. The analysis of literary sources of domestic and foreign authors was carried out. In recent years, various methods have been proposed and used to minimize postoperative effects, such as the introduction of platelet-enriched fibrin, the use of lasers, cryotherapy, injections of various drugs, and the formation of various forms of muco-oxidative flaps. A wide range of techniques allows the dentist to minimize the risk of iatrogenic complications. But currently, the features of preventive measures that allow the dentist to create a physiological optimum for such a widespread surgical dental intervention as the extraction of the mandibular third molar are not sufficiently substantiated.